تنفيذ ألعاب دولينجو التعليمية في زيادة قراءة المحارة لدى الطلاب - Sinta Amalia, Muhammad Alfayed (PT Wahana Global Education, 2025)
This research aims to develop Arabic language skills by using educational game media, where each game has a different level, so that it can support student learning. The method used is descriptive qualitative by conducting a literature study, data was taken from students who used the Duolingo game application. The results of this research found that the Duolingo game can improve reading skills, although this game can also train other skills such as maharah istima' and kitabah, but it is not as intense as practicing maharah qiraah.